Edukasi kesehatan kepada orangtua melalui asuhan keperawatan keluarga dalam pencegahan stunting pada balita - Dava Arya Putra; Rudi Winarno; Eka Trismiyana (JOURNAL of Public Health Concerns, 2026)
Background: Stunting is a chronic nutritional issue that impacts child growth and development. According to the WHO (2023), 148 million children under five worldwide suffer from stunting. In Indonesia, the stunting prevalence was 21.6% in 2022; in Lampung Province, it was 15.9% in 2024; and in Bandar Lampung City, it was 14.8%, with 27 cases recorded in the Panjang Community Health Center area. Health education for parents serves as a stunting prevention strategy by improving knowledge and behaviors regarding the fulfillment of children's nutritional needs. Therefore, nursing care focused on stunting prevention for children under five delivered through health education for parents was implemented at the Panjang Community Health Center in Bandar Lampung City in 2026. Purpose: To provide direct education through nursing care to parents regarding stunting prevention. Method: This activity involved nursing care using a case study approach, conducted from January to February 2026 at the Panjang Community Health Center, Bandar Lampung City. The population consisted of 14 families with children under five showing indications of stunting. Through purposive sampling, two families with children diagnosed with stunting and for whom the nursing diagnosis was "deficient knowledge" were selected. The educational content covered measurements of weight, height, and head circumference (compared against age-based standards); the frequency of breastfeeding and complementary feeding; the child's daily diet; and the parents' level of understanding regarding balanced nutrition and growth and development stimulation. Evaluation was conducted by assessing questionnaire scores obtained before (pre-test) and after the educational activity. Results: An improvement in understanding regarding child growth and development was observed, evidenced by the monitoring of weight and height relative to age, an understanding of necessary nutritional intake and portion sizes, and health consultations with healthcare facilities regarding stunting. Respondent 1’s knowledge score (percentage of correct answers) was 20% prior to the educational activity and rose to 80% afterward. Meanwhile, Respondent 2’s knowledge score was 40% before the activity and increased to 90% after the activity. Conclusion: Direct educational activities combined with nursing care for families affected by stunting are highly effective in enhancing family knowledge and understanding regarding the management of stunting. Increased parental understanding of stunting also fosters greater awareness of adopting healthy lifestyle behaviors, thereby aiding in the recovery of affected children and the prevention of stunting. Keywords: Balanced nutrition; Health education; Nursing care; Stunting Pendahuluan: Stunting merupakan masalah gizi kronis yang berdampak pada pertumbuhan dan perkembangan anak. Menurut WHO tahun 2023, sebanyak 148 juta balita di dunia mengalami stunting. Di Indonesia, prevalensi stunting tahun 2022 sebesar 21.6%, sedangkan di Provinsi Lampung tahun 2024 sebesar 15.9% dan di Kota Bandar Lampung sebesar 14.8%, dengan 27 kasus di wilayah Puskesmas Panjang. Pendidikan kesehatan kepada orang tua menjadi salah satu upaya pencegahan stunting karena dapat meningkatkan pengetahuan dan perilaku dalam pemenuhan gizi anak. Oleh karena itu, dilakukan asuhan keperawatan kepada orang tua dalam pencegahan stunting pada balita melalui pendidikan kesehatan di Puskesmas Panjang Kota Bandar Lampung tahun 2026. Tujuan: Untuk memberikan edukasi langsung dengan melakukan asuhan keperawatan kepada orangtua dalam pencegahan stunting. Metode: Kegiatan ini merupakan asuhan keperawatan dengan pendekatan studi kasus yang dilaksanakan pada bulan Januari-Februari 2026 di Puskesmas Panjang Kota Bandar Lampung. Populasi dalam kegiatan ini adalah 14 keluarga dengan balita yang terindikasi stunting. Dengan teknik purposive sampling mendapatkan 2 keluarga pasien stunting dengan diagnosis keperawatan defisit pengetahuan. Materi penyuluhan meliputi pengukuran berat badan, tinggi badan, dan lingkar kepala untuk bandingkan dengan standar usia, frekuensi pemberian ASI/MPASI, dan jenis makanan harian anak serta tingkat pemahaman orang tua mengenai gizi seimbang dan stimulasi tumbuh kembang. Evaluasi dilakukan dengan melakukan pengkajian skor kuesioner yang diberikan sebelum kegiatan (pretest) dan sesudah kegiatan edukasi. Hasil: Menunjukkan peningkatan pemahaman tentang tumbuh kembang anak dengan memonitor berat badan dan tinggi badan sesuai usianya, memahami kebutuhan asupan gizi dan porsi makan yang harus dipenuhi, dan melakukan konsultasi kesehatan terkait stunting kepada fasilitas kesehatan. Tingkat pengetahuan responden 1 mendapatkan jawaban benar sebelum kegiatan edukasi sebanyak 20% dan meningkat setelah kegiatan edukasi menjadi sebanyak 80%. Sedangkan pengetahuan responden 2 mendapatkan jawaban benar sebelum kegiatan edukasi sebanyak 40% dan meningkat setelah kegiatan edukasi menjadi sebanyak 90%. Simpulan: Kegiatan edukasi langsung dengan asuhan keperawatan pada keluarga dengan stunting sangat efektif meningkatkan pengetahuan dan pemahaman keluarga untuk mengatasi masalah kejadian stunting. Meningkatnya pemahaman orang tua terhadap kejadian stunting juga memberikan dampak pada kesadaran dalam menerapkan perilaku hidup sehat dalam membantu pemulihan dan pencegahan anak dengan masalah stunting.